Exploring the factors enhancing marketability of coastal agricultural products in rural South Africa - Ifeanyi Mbukanma; Vikela Liso Sithole; Yiseyon Sunday Hosu (Economies, 2025)
This study explores the dynamics of marketing agricultural products in the coastal regions of the Eastern Cape, South Africa, through an analysis of existing literature and empirical data collected from selected participants to model farmers' marketing experiences and identifies an improvement pathway. This study aims to enhance the understanding of the factors that inhibit and enable the marketability of coastal agricultural products. Employing a causal relationship research methodology, this paper reviewed the current situation through a bottom-up approach, providing valuable insights for policymakers, interventionists, researchers, and practitioners who aim to support rural coastal agricultural growth and livelihood enhancement in the Eastern Cape. Data were collected from 215 participants from the sample of 4212 registered coastal small-scale farms in the Eastern Cape through a multi-staged sampling procedure. The findings through Path analysis empirically revealed that technological resources, efficient supply chain systems, supportive government policies, and unlimited market access significantly enhance the marketability of coastal agricultural products. The study recommends addressing challenges such as inadequate infrastructure, stringent regulatory requirements, and the effects of climate change, which is essential for advancing the marketability of coastal agricultural products.
Keywords: 330; coastal agriculture; marketability; agricultural products; Eastern Cape